МЕТОДИЧЕСКИЙ ПОДХОД К ОЦЕНКЕ ИСХОДНОЙ СИТУАЦИИ ДЛЯ РАЗРАБОТКИ СИСТЕМЫ ЭКОЛОГИЧЕСКОГО МЕНЕДЖМЕНТА ПО СТАНДАРТУ ISO 14001: 2004 (НА ПРИМЕРЕ МЕТАЛЛУРГИЧЕСКОГО ПРЕДПРИЯТИЯ) - Костылева (Kostileva Natalia) Наталья Валерьевна; Микишева (Mikischeva Valentina) Валентина Ивановна; Сорокина (Sorokina Tatiana) Татьяна Васильевна (Географический вестник=Geographical bulletin, 2017)
Изложен методический подход к оценке исходной ситуации для разработки и внедрения в дальнейшем на предприятии системы экологического менеджмента по международному стандарту ISO 14001: 2004[1]. Этот подход апробирован на одном из крупнейших металлургических предприятий России. Рассмотрены результаты апробации. Сделан вывод о наличии элементов системы экологического менеджмента в природоохранной деятельности предприятия, основанной на соблюдении законодательства. METHODICAL APPROACH TO THE ESTIMATION OF THE INITIAL SITUATION FOR SYSTEM ENGINEERING OF ENVIRONMENTAL MANAGEMENT UNDER STANDARD ISO 14001: 2004 (ON EXAMPLE OF THE METALLURGICAL ENTERPRISE) A propose of specific methodical approach to Preliminary Condition Estimation (PCE) of existing environmental activities in correspondence with requirements of the ISO 14001:2004 standard (on example of the metallurgical enterprise). The approach consists of three consecutive stages. First and the most important stage is the evaluation of environmental documents and activity processes with requirements of Russian environmental legislation. This stage allows identifying some documented significant environmental aspects on the beginning of the checking and reducing costs of estimation for the enterprise. PCE shows the enhanced environmental activities organized with requirements of Russian environmental legislation has some elements of Environmental management systems and can be good base of it.